Strategi Komunikasi Dosen Dalam Menerapkan Pembelajaran Daring Pada Mahasiswa - Riastri Rias Novianita; Cindya Yunita Pratiwi (JURNAL PETIK, 2022)
Abstract — Communication comes from the Latin communis which means the same. Communication occurs when there are similarities between the delivery of the message and the person who receives the message. Therefore, communication depends on the ability to be able to understand one another. Communication is used to meet organic needs. In general, human communication is described as signal language, speech, writing, movement, and broadcasting. This form of communication can be in the form of interactive, transactive, purposeful, to aimless. By communicating, the attitudes and feelings of a person or group can be understood by other parties. Communication will be effective if the message conveyed can be understoodThe purpose of communication is to change attitudes, opinions, behavior, and social. So in essence, communication aims to convey information that can be understood by others. Lecturer as educators, facing on the covid pandemic, must have the right online learning strategy, so that the teaching to students can delivered effective.Keywords — Communication,Educator,Lecturer, Message,Pandemic Abstrak — Komunikasi berasal dari bahasa latin communis yang artinya sama. Komunikasi terjadi ketika ada kesamaan antara penyampaian pesan dan orang yang menerima pesan. Oleh karena itu, komunikasi tergantung pada kemampuan untuk dapat memahami satu sama lain. Komunikasi digunakan untuk memenuhi kebutuhan organik. Secara umum, komunikasi manusia digambarkan sebagai bahasa isyarat, ucapan, tulisan, gerakan, dan penyiaran. Bentuk komunikasi ini dapat berupa interaktif, transaktif, terarah, hingga tanpa tujuan. Dengan berkomunikasi, sikap dan perasaan seseorang atau kelompok dapat dipahami oleh pihak lain. Komunikasi akan efektif jika pesan yang disampaikan dapat dipahamiTujuan komunikasi adalah untuk mengubah sikap, pendapat, perilaku, dan sosial. Jadi pada hakikatnya, komunikasi bertujuan untuk menyampaikan informasi yang dapat dipahami oleh orang lain. Dosen sebagai pendidik, menghadapi pandemi covid, harus memiliki strategi pembelajaran online yang tepat, agar pengajaran kepada mahasiswa dapat tersampaikan dengan efektif.Kata kunci— Komunikasi, Pendidik, Dosen, Pesan, Pandemi